2006
DOI: 10.1002/adfm.200600336
|View full text |Cite
|
Sign up to set email alerts
|

Low Electrical Percolation Threshold of Silver and Copper Nanowires in Polystyrene Composites

Abstract: Silver and copper nanowires have been synthesized using a scalable method of AC electrodeposition into porous aluminum oxide templates, which produces gram quantities of metal nanowires ca. 25 nm in diameter and up to 5 and 10 μm in length for Ag and Cu, respectively. The nanowires have been used to prepare polystyrene nanocomposites by solution processing. Electrical resistivity measurements performed on polymer nanocomposites containing different volume fractions of metal indicate that low percolation thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(146 citation statements)
references
References 64 publications
4
141
1
Order By: Relevance
“…[46] In a 3-D composite consisting of a mixture of conducting rods in a polymer matrix, the rods tend to be randomly dispersed throughout a matrix, leading to a slightly differnet percolation scaling law which depends on the filler volume fraction, : S/m to σ ~ 10 4 S/m, which correlates to the theoretical value predicted by SEM for the first conductive pathway to form. The percolation threshold values reported here in this work were found to be in good agreement with other values calculated in literature for both layered [49] and mixed [50] composites using AgNWs of similar dimensions. From the electrical characterisation, it is very much apparent that the LBL method of composite production is superior to its mixed composite counterpart due to its much lower percolation threshold.…”
Section: Composite Electrical Propertiessupporting
confidence: 91%
“…[46] In a 3-D composite consisting of a mixture of conducting rods in a polymer matrix, the rods tend to be randomly dispersed throughout a matrix, leading to a slightly differnet percolation scaling law which depends on the filler volume fraction, : S/m to σ ~ 10 4 S/m, which correlates to the theoretical value predicted by SEM for the first conductive pathway to form. The percolation threshold values reported here in this work were found to be in good agreement with other values calculated in literature for both layered [49] and mixed [50] composites using AgNWs of similar dimensions. From the electrical characterisation, it is very much apparent that the LBL method of composite production is superior to its mixed composite counterpart due to its much lower percolation threshold.…”
Section: Composite Electrical Propertiessupporting
confidence: 91%
“…Micrometer (5 and 10 μm) long Ag and Cu nanowires having a diameter of 25 nm fabricated using template based method mixed with polystyrene. The composites attained a low percolation at a 0.25 and 0.75 vol% (Gelves et al 2006). Further study showed that unfunctionalized Cu nanowires having a diameter of 25 nm and length 1.78 μm able to form electrical conductive networks at 0.5 vol% whereas for functionalized nanowires it is 0.25 vol%.…”
Section: Nanowire Compositesmentioning
confidence: 98%
“…With this goal in mind, elongated fillers with diameters on the micron scale, such as stainless steel fibers or metallized glass fibers, were already being employed in the early 1980s [8]. In nanocomposites, in addition to CNTs, insulating polymers have also been loaded with short conducting carbon fibers [11] and metal nanowires [12,13].…”
Section: Introductionmentioning
confidence: 99%